Developing lifelong learners: a novel online problem-based ultrasonography subject - Minasian-Batmanian , Laura C.; Koppo , Anthony J.; Pearson , Elaine J. (Research in Learning Technology, 1970)
There have been significant advances in the practice of sonography since the introduction of the University of Sydney course in 1991. The entire knowledge base can no longer be taught within the constraints of time allotted to the subject. Moreover, encouraging students to be self-directed, independent learners is more important than ever, since the field of sonography has reached a stage where there is an urgent need for new skills.DOI:10.1080/0968776000080106